2015
DOI: 10.5194/bg-12-2395-2015
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton dynamics in contrasting early stage North Atlantic spring blooms: composition, succession, and potential drivers

Abstract: Abstract. The spring bloom is a key annual event in the phenology of pelagic ecosystems, making a major contribution to the oceanic biological carbon pump through the production and export of organic carbon. However, there is little consensus as to the main drivers of spring bloom formation, exacerbated by a lack of in situ observations of the phytoplankton community composition and its evolution during this critical period.We investigated the dynamics of the phytoplankton community structure at two contrastin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 62 publications
4
21
0
Order By: Relevance
“…This contradicts the general view of the typical spring diatom assemblages often being dominated by large species, such as Pseudo-nitzschia and large Chaetoceros, (e.g. Ribera d'Alcalà et al 2004;Daniels et al 2015). However, Daniels et al (2015), who investigated the dynamics of the phytoplankton community structure at two contrasting sites in the Icelandic and Norwegian basins, found that the typical large diatoms dominated the spring bloom in the Icelandic basin, while very small (even <5 µm) diatoms dominated in the Norwegian basin.…”
Section: Seasonal Cyclementioning
confidence: 70%
“…This contradicts the general view of the typical spring diatom assemblages often being dominated by large species, such as Pseudo-nitzschia and large Chaetoceros, (e.g. Ribera d'Alcalà et al 2004;Daniels et al 2015). However, Daniels et al (2015), who investigated the dynamics of the phytoplankton community structure at two contrasting sites in the Icelandic and Norwegian basins, found that the typical large diatoms dominated the spring bloom in the Icelandic basin, while very small (even <5 µm) diatoms dominated in the Norwegian basin.…”
Section: Seasonal Cyclementioning
confidence: 70%
“…Nevertheless the large size range of the diatoms, from nanosized to microsized classes, is not taken into account with the method used in our study to determine the phytoplankton community structure [ Uitz et al ., ]. While previous studies in the NWM observed diatoms bloom of the microphytoplankton size class [ Percopo et al ., ; Rigual‐Hernández et al ., ], it is possible that smaller diatoms taxa become dominant like in the North Atlantic spring bloom because of changes in the environmental conditions [ Daniels et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Temperature was recorded at 15 min intervals using Hobo data loggers. To recreate the ambient in situ light environment, the deck incubators were covered with an optical filter (light blue #118 LEE™), which was chosen to best represent the light attenuation and spectral quality within the mixed layer by transmitting light in the 400–570 nm range and removing longer wavelengths (Daniels et al and references within). Based on comparisons between the on‐deck incoming irradiance and the light intensity inside the screened incubator measured with a Biospherical QSL‐2101 light meter, the filter reduced the overall light to ca.…”
Section: Methodsmentioning
confidence: 99%